PERANAN PUSAT PELATIHAN PERTANIAN PEDESAAN SWADAYA (P4S) DALAM PEMBERDAYAAN PETANI DI KABUPATEN LAMPUNG TENGAH - Rokhma Yeni; Dewangga Nikmatullah; Rio Tedi Prayitno (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aimed to analyze the role of rural agriculture training centre (P4S) on empowering farmers and find out the factors related to the role. This research was conducted in four P4S in Central Lampung Regency, those are Mitra Tani Mandiri, P4S Sama Maju, P4S Ras Andani, and P4S Budidaya. Respondents of this research were 74 people that consist of 23 facilitators and 51 farmers. The data were collected in February - March 2018. The role of P4S was analyzed descriptively and hypothesis was analyzed using Rank Spearman correlation. The results of this research showed that the role of P4S on empowering farmers in Centre Lampung Regency is included in moderate classification. The internal factors such as work motivation, cosmopolitan character, and the external factor that is reward system don’t have significant relation to the role of P4S on empowering farmers. Availability of facilities-infrastructure and the number of assisted farmers have significant relationship to the role of P4S on empowering farmers in Central Lampung Regency. Key words : empowering farmers, P4S, role